2023
DOI: 10.1038/s41598-023-32733-y
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of LPAR5 gene in prognosis and immunity of thyroid papillary carcinoma and pan-cancer

Abstract: Papillary carcinomas account for the largest proportion of thyroid cancers, with papillary thyroid carcinoma (PTC) being prone to early lymph node metastasis. Some studies have confirmed that LPAR5 can promote the progression of PTC, but immune-related analyses of LPAR5 and PTC have not been widely discussed. This study aimed to determine the role of LPAR5 in PTC prognosis and immunity. We will further explore the role of LPAR5 in 33 different tumor types. Regarding PTC, we analyzed the effect of LPAR5 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Lysophosphatidic acid receptor 5 (LPAR5) is considered a prognosis-related gene for pan cancers, and abnormal high-level expression of LPAR5 confers IR-induced epithelial-to-mesenchymal transition (EMT) and radioresistance to cancer cells [ 17 , 70 ]. Recently, our group identified that the A1881 in LPAR5 mRNA 3′UTR is an M6A-modified site mediated by METTL3, which determines the stability of LPAR5 mRNA [ 44 ].…”
Section: M6a Methylation In Rna During Cellular Responses To Cancer R...mentioning
confidence: 99%
“…Lysophosphatidic acid receptor 5 (LPAR5) is considered a prognosis-related gene for pan cancers, and abnormal high-level expression of LPAR5 confers IR-induced epithelial-to-mesenchymal transition (EMT) and radioresistance to cancer cells [ 17 , 70 ]. Recently, our group identified that the A1881 in LPAR5 mRNA 3′UTR is an M6A-modified site mediated by METTL3, which determines the stability of LPAR5 mRNA [ 44 ].…”
Section: M6a Methylation In Rna During Cellular Responses To Cancer R...mentioning
confidence: 99%